1993
DOI: 10.1193/1.1585722
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Mechanical Damping Devices Tested at Real Earthquake Displacements

Abstract: Experimental steady-state hysteretic characteristics of ten direct shear seismic damping devices (DSSDs) are presented. The devices were tested over a range of frequencies and displacements chosen as representative of building responses during moderate to severe level earthquakes. Three different damping materials, produced by 3M Corporation and Lord Corporation, were used in the devices. Excitation frequency, strain amplitude, damping material initial temperature, temperature change over the test duration, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Viscoelastic devices response under sinusoidal loading, the stress will be proportional to the strain and the phase angle, and thus the strain has the form and calculated by equation Where G * is complex shear modulus G 1 and G 2 referred to as the storage and loss modulus respectively. Different vibrant tests of a wide range of several frames with VEDs have been carried out [63][64][65][66][67][68]. Full-scale viscoelastic coupling damper (VCD) test was performed to control the response for the application of dampers in Toronto and Vancouver, to establish the large displacement demand [69].…”
Section: Viscoelastic Devices (Veds)mentioning
confidence: 99%
“…Viscoelastic devices response under sinusoidal loading, the stress will be proportional to the strain and the phase angle, and thus the strain has the form and calculated by equation Where G * is complex shear modulus G 1 and G 2 referred to as the storage and loss modulus respectively. Different vibrant tests of a wide range of several frames with VEDs have been carried out [63][64][65][66][67][68]. Full-scale viscoelastic coupling damper (VCD) test was performed to control the response for the application of dampers in Toronto and Vancouver, to establish the large displacement demand [69].…”
Section: Viscoelastic Devices (Veds)mentioning
confidence: 99%
“…Many performance tests on small-scale and full-scale VE dampers were conducted to investigate their force-deformation (or stress-strain) relationship and the effects of displacement amplitudes, excitation frequencies, ambient temperatures, temperature rises, softening, hardening, and cumulative energy absorption on their mechanical behavior. [2][3][4][5][6][7] With performance test verification, different methods for mathematically modeling the mechanical behavior of VE dampers (or material) were presented, such as the fractional derivative model, [8][9][10][11] equivalent fractional Kelvin model, 6 VE solid model, 12 classical model, 13 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have been conducted to derive analytical models for VED and to verify the effect on structural control through experiments [3]- [6]. Previous studies showed that VED can increase structural damping significantly, which brings the decrease of structural responses, such as displacement and absolute acceleration.…”
Section: Introductionmentioning
confidence: 99%